FACTORS AFFECTING WORKING CAPITAL NEEDS IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2015-2020 - OK Sofyan Hidayat; Muhammad Ridha Habibi; La Ane; Amrullah Amrullah (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
The problem in this research is how the company manages their working capital properly with understanding the determinants of working capital for the company to avoid the risk of bankruptcy. This study aimed to examine the effect of leverage, operating cash flow, profitability, sales growth, company size, sales fluctuations, the age of the company, and cash conversion cycle to the working capital requirements individually. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange asmany as 132 companies. The sampling method using purposive sumpling and obtained 80 companies as samples  in 2015-2020. The data used in this research is secondary data in the form of financial statements that are downloaded from www.idx.co.id. Data analysis technique used is multiple linear regression. The results showed that leverage, profitability, company size, and the cash conversion cycle significantly influence working capital requirements. These results indicate that the debts of the company, profitability, company size, and the cash conversion cycle, are all factors that must be considered by the company in determining the policies of proper management of working capital with under 5% significant. In connection with the pecking order theory, companies should not use too high debt if they have an advantage in the form of income, asset, and a high cash flow, which can be used to invested in working capital.